EFFECTS OF DIFFERENT SALINITY LEVELS ON PHYSIOLOGICAL AND HEMATOLOGICAL RESPONSE OF ROCK BREAM Oplegnathus fasciatus - Vitas Atmadi Prakoso; Jun Hyung Ryu; Byung Hwa Min; Rudhy Gustiano; Young Jin Chang (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2016)
Rock bream Oplegnathus fasciatus is one of economically important marine fish species in East Asia. However, lack of information about the salinity tolerance of rock bream related to its physiological response made this issue were needed to be studied. The present study was conducted to determine the effects of different salinity levels on physiological and hematological response of rock bream in order to obtain its salinity tolerance. Twelve rock breams (total length: 26.9 ± 0.6 cm, body weight: 477.3 ± 61.9 g) were used for experiments. Four experimental groups with three replications were conducted to measure the effects of salinity (5, 15, 25, and 35 practical salinity unit (psu)) on physiological and hematological response of rock bream. Fish were stocked into the chamber inside the closed recirculation system. At the end of each experiment, blood samples were collected. The study revealed that lower salinity exposure had tendency to decrease the physical and chemical properties of blood in rock bream. The value of Na+, Cl-, Ca, Mg, and osmolality showed tendency to decrease with lowering salinity, while cortisol and glucose showed tendency to increase from 35 psu to low salinity environment, indicating the enhancement of fish stress and resulted in fish mortality at 5 psu. The lowest cortisol value was 76.3 ng/mL in 25 psu, and the highest value was 188.8 ng/mL in 5 psu. Meanwhile, the lowest glucose value was 35.3 mg/dL and the highest value was 166.7 mg/dL (P<0.05). Results indicate that rock bream could tolerate lower salinity up to 15 psu.